Drivers of Employee Engagement among Generation Z: The Role of Servant Leadership, Creative Self-Efficacy, Learning Climate, and Organizational Trust - Muhammad Alex Davidson; Emma Yulianti (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines the effect of servant leadership, creative self-efficacy, learning climate, and organizational trust on employee engagement among Generation Z employees in East Java. Methodology: A quantitative approach was employed using questionnaire data collected from Generation Z employees in various organizations in East Java and analyzed using statistical techniques. Results: The results show that servant leadership, creative self-efficacy, learning climate, and organizational trust have a significant positive effect on employee engagement.  Findings: The findings indicate that for Generation Z employees, engagement is driven less by traditional control mechanisms and more by developmental leadership, psychological safety to express creativity, and a trustworthy organizational environment. Novelty: The novelty of this study lies in its integrated multi-level model that simultaneously examines leadership, individual psychological resources, and organizational context in explaining employee engagement among Indonesian Generation Z workers. Originality: The originality of this research is reflected in its specific focus on Generation Z employees in East Java, a context that has received limited attention in previous studies. Conclusion: Strengthening servant leadership, developing creative self-efficacy, fostering a positive learning climate, and enhancing organizational trust are essential to improve employee engagement. Type of Paper: Empirical Research Paper.